Komunikasi Sosial BP4 (Badan Penasihatan Pembinaan dan Pelestarian Perkawinan) dalam Mencengah Pernikahan Usia Muda di Kecamatan Kualuh Hilir - Saniah, Nurul (Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Marriage is a means of embodiment of affection between a woman and a man. It is different if a young marriage is more likely to cause many problems in building a household. Social communication is one of the communications carried out by a group of people in socializing BP4 activities. BP4, which was formerly under the auspices of the ministry of religion, and has now been replaced by the ministry of religion, is a non-political organization from the central to the village level that is tasked with dealing with social problems such as divorce, divorce, reconciliation, and young marriages, especially those in Kualuh Hilir District.The purpose of this study was to find out the activities carried out by BP4 in middle age marriages in Kualuh Hilir District.The method used in this study is a qualitative method which emphasizes research conducted by interviews and direct observation of research subjects. After conducting this research, it is hoped that BP4 can prevent young marriages in the Kualuh Hilir District. In addition, BP4 also has a very important role in society because many of the activities carried out by BP4 have a positive impact on society, especially in preventing young marriages. In preventing young marriages, social communication is carried out by BP4 through activities in the community such as giving religious lectures, seminars, sakinah family competitions, and counseling. This activity is expected to have a positive impact on society.